Pathogen effector recognition-dependent association of NRG1 with EDS1 and SAG101 in TNL receptor immunity - Sun, Xinhua (Nat Commun, 2021)
Plants utilise intracellular nucleotide-binding, leucine-rich repeat (NLR) immune receptors to detect pathogen effectors and activate local and systemic defence. NRG1 and ADR1 “helper” NLRs (RNLs) cooperate with enhanced disease susceptibility 1 (EDS1), senescence-associated gene 101 (SAG101) and phytoalexin-deficient 4 (PAD4) lipase-like proteins to mediate signalling from TIR domain NLR receptors (TNLs). The mechanism of RNL/EDS1 family protein cooperation is not understood. Here, we present genetic and molecular evidence for exclusive EDS1/SAG101/NRG1 and EDS1/PAD4/ADR1 co-functions in TNL immunity. Using immunoprecipitation and mass spectrometry, we show effector recognition-dependent interaction of NRG1 with EDS1 and SAG101, but not PAD4. An EDS1-SAG101 complex interacts with NRG1, and EDS1-PAD4 with ADR1, in an immune-activated state. NRG1 requires an intact nucleotide-binding P-loop motif, and EDS1 a functional EP domain and its partner SAG101, for induced association and immunity. Thus, two distinct modules (NRG1/EDS1/SAG101 and ADR1/EDS1/PAD4) mediate TNL receptor defence signalling.